PERANCANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMA NEGERI 3 SUKOHARJO - Hasan, Fuad Nur; Pratama, Eka Kusuma (EDUTECH CONSULTANT, 2018)
The process of delivering information in SMAN 3 Sukoharjo is still using the manual system. With a system like this, certainly it will slow down the process of delivering information. Delivery errors occur when information is often still being done by manual systems. In order to speed up the delivery of information and reducing information delivery errors, it requires a web-based information systems academic. With internet media intermediaries’ course, information process will be faster. Academic information systems development methods, the authors used in designing a good system is to use the waterfall method. For a proposed database design Entity Relationship Diagram (ERD) and Logical Record Structure (LRS). Data was collected through observation, interviews, and literature. Implementation of the program using Adobe Dreamweaver CS6 with a MySQL database by using phpMyAdmin. With the system he designed a web-based academic information in SMAN 3 Sukoharjo expected process of delivering information to more effectively and efficiently, so that the school community, especially students and teachers can find the information anytime and anywhere.